Structural and evolutionary genomics : natural selection in genome evolution - Bernardi, Giorgio (New comprehensive biochemistry ;, 2005)
Structural genomics is the study of the DNA of living organisms. Evolutionary genomics is the study of the history of the genome. These subjects are closely interlinked. They are approached in this book using as a guideline the investigations carried out in the author's laboratory, relevant literature is critically reviewed and some general conclusions are presented. The author and his collaborators have studied a vast number of genomes, ranging from prokaryotes to human, using different approaches, including physical chemistry of DNA, viral integration and molecular cytogenetics.